2015
DOI: 10.1039/c5dt00955c
|View full text |Cite
|
Sign up to set email alerts
|

Insertion, elimination and isomerisation of olefins at alkylaluminium hydride: an experimental and theoretical study

Abstract: The insertion, elimination and isomerisation of octenes with di-n-octylaluminium hydride [HAl(Oct)2], tri-n-octylaluminium [Al(Oct)3] and sec-octylaluminium species have been studied as individual steps in a putative aluminium based contrathermodynamic olefin isomerisation process. While elimination of 1-octene from [Al(Oct)3] is energetically unfavourable, the process is driven by high temperature vacuum distillation, leading to very high selectivity to 1-octene (>97%). At high conversions the [HAl(Oct)2] so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…14 In contrast, in the presence of catalytic 5 or 6 (5-10 mol%), insertion proceeds rapidly at room temperature and is essentially complete (>97%) within 15 minutes. We previously demonstrated that at 75°C 1-octene inserts with a half-life of around 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In contrast, in the presence of catalytic 5 or 6 (5-10 mol%), insertion proceeds rapidly at room temperature and is essentially complete (>97%) within 15 minutes. We previously demonstrated that at 75°C 1-octene inserts with a half-life of around 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The cycle relies on the tendency of some transition metal and group 13 metal secondary alkyls to rearrange to the thermodynamically preferred primary alkyl by way of chain walking. [13][14][15] The cycle relies on the tendency of some transition metal and group 13 metal secondary alkyls to rearrange to the thermodynamically preferred primary alkyl by way of chain walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The conversion of internal olefins into α-olefins, which is a contrathermodynamic process, is therefore required in order to develop an overall n-alkane to LAO conversion process. For this reason, we have recently 13,14 been investigating the individual steps of the cycle shown in Scheme 1 as a potential method for internal to α-olefin conversion, which involves three steps. The first is insertion of an internal olefin into a metal-hydride bond to yield a sec-alkylmetal compound.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 On the other hand, we showed that α-olefins can be removed from tri-n-alkylaluminium with very high selectivity (>97%), but in this case insertion and isomerisation of internal olefins was unsuccessful. 14 The reaction of [Al(n-Alk) 2 H] with internal olefins reaches an equilibrium position (ca. 50% insertion), and isomerisation to the more stable primary alkyl is too slow to drive the reaction to completion.…”
Section: Introductionmentioning
confidence: 99%